Clinical Outcomes of Emergent Laparotomies in Hypotensive Patients: 9-years Experience at a Single Level 1 Trauma Center - Yoo, Jaeri; Kang, Byung Hee (Journal of acute care surgery, 2021)
Purpose: The prognosis of an emergent laparotomy in hypotensive patients is poor. This study aimed to review the outcomes of hypotensive patients who had emergent laparotomies and elucidate the risk factors of mortality.Methods: Patients who underwent an emergent laparotomy from January 2011 to December 2019 were retrospectively reviewed. The exclusion criteria included initial systolic blood pressure > 90 mmHg, aged < 19 years, and cardiac arrest before the laparotomy. Patients were categorized into survival groups (survived or deceased). Univariate and multivariate analyses were conducted to determine the risk factors of mortality. The time from the laparotomy to death was also reviewed and the effect of organ injury.Results: There were 151 patient records, analyzed 106 survivors, and 45 deceased. The overall mortality was 29.8%. Liver injury was the main organ-related event leading to an emergent laparotomy, and most patients died in the early phase following the laparotomy. Following multivariate analysis, the Glasgow Coma Scale score [odds ratio (95% confidential interval) 0.733 (0.586-0.917), p = 0.007], total red blood cell transfusion volume in 24 hours[1.111 (1.049-1.176), p < 0.001], major bleed from the liver [3.931 (1.203-12.850), p = 0.023], and blood lactate [1.173 (1.009-1.362), p = 0.037] were identified as risk factors for mortality.Conclusion: Glasgow Coma Scale score, total red blood cell transfusion volume in 24 hours, major bleed from the liver, and lactate were identified as risk factors for mortality. Initial resuscitation and management of liver injuries have major importance following trauma.